A Comprehensive Review of Formulation, Characterization, and Applications of Solid Dispersions in Drug Delivery - Hazbar, Noor Sabah; Abood, Ahmed Najim (American Journal of Biomedicine and Pharmacy, 2025)
Many recently produced drug candidates still face formulation challenges due to low water solubility, which limits their oral bioavailability and therapeutic efficacy. A method that shows promise for increasing the solubility and the rate of dissolution of medications that are not very soluble in water is solid dispersion (SD) technology. To improve wettability, surface area, and dissolution kinetics, SDs can convert crystalline pharmaceuticals into amorphous forms with higher energy levels by dispersing the drug at the level of molecules or particles in an inert carrier matrix, usually a polymer. Solid dispersions are made employing various techniques, such as solvent evaporation, hot-melt extrusion, and spray drying. To solidify the amorphous state and prevent recrystallization, Poloxamers, PVP, PEGs, and Soluplus® are examples of polymers that are widely used. The latest developments in SD formulation are examined in this abstract.